Methodological Triangulation In Movement Pattern Research - Kotus, Jacek; Rzeszewski, Michał (Quaestiones Geographicae, 2015)
The application of GIS and GPS methods together with qualitative sociological methods is one of the current fields of discussion in studies of human behaviour in space. The authors ask about the justification, manner and value of using the ‘triad’: quantitative GIS measurement methods – qualitative sociological methods – quasi-experiment. A mixed-method approach in an analysis of human movement patterns is introduced. Also, the role of the investigator in such projects is discussed.